Towards a Comprehensive Edition of the Arabic-Ethiopic Glossary of al-Malik al-Afḍal Part I: New Readings from the First Sheet - Bulakh, Maria; Kogan, Leonid (Aethiopica, 2013)
The paper presents the preliminary results of a thorough palaeographic and etymological analysis of the first sheet of the al-Malik al-Afḍal’s 14th century Arabic–Ethiopic Glossary, undertaken by the team of Russian scholars in the framework of a project on edition and publication of the whole Glossary. The results are compared with the identifications offered recently by Franz-Christoph Muth. For the 34 entries from the first sheet of the Glossary, whose identification in Muth’s publication is either missing altogether or not sufficiently convincing, new identifications are offered and discussed.